Stylistic Characteristics Of Some Lexical Units Used In Uzbek Dramas - Sharifa Madaliyevna Iskandarova; Gulhida Axmadillo qizi Ikromova (Zien Journals, 2022)
This article discusses some of the considerations for the lexical analysis of Uzbek dramatic works and the role of lexemes of a limited layer in enhancing the artistic effectiveness of these works
Keywords: Drama; slang; argot; barbarism